INSTITUTIONAL ENVIRONMENT AND MARKET STRUCTURE AS DRIVERS OF BANKING INDUSTRY PERFORMANCE - Muñoz Mendoza, Jorge A.; Veloso Ramos, Carmen L.; Delgado Fuentealba, Carlos L. (Investigación Económica, 2024)
We analyze the effects of market concentration, income diversification, and institutional environment on banking industry performance. We used a sample of 168 countries for the 1994-2019 period and the GMM estimators for dynamic panel data regressions. Our results show that market concentration and diversification have a positive effect on bank performance. The institutional environment, both public-political and private-regulatory, has a negative effect on bank profitability, showing that these financial institutions obtain higher returns in countries with institutional weaknesses. When countries have a high institutional quality, the positive impact of market concentration and income diversification is reversed. Strengthening countries’ institutional quality makes it possible to combine competition between banks and specialization in traditional activities with higher performance. These results are relevant for bank stability and financial policy design, given that the institutional framework includes both direct and indirect channels that affect the general behavior and strategies of banks in the industry. ENTORNO INSTITUCIONAL Y ESTRUCTURA DEL MERCADO COMO IMPULSORES DEL DESEMPEÑO DE LA INDUSTRIA BANCARIA RESUMEN Analizamos los efectos de la concentración del mercado, la diversificación de ingresos y el entorno institucional en el desempeño de la industria bancaria. Usamos una muestra de 168 países para el periodo 1994-2019 y estimadores GMM para regresiones de datos de panel dinámicos. Nuestros resultados muestran que la concentración y diversificación del mercado tienen un efecto positivo en el desempeño bancario. El entorno institucional, tanto público-político como privado-regulatorio, tiene un efecto negativo sobre la rentabilidad que muestra que el sistema bancario obtiene mayores retornos en naciones con debilidades institucionales. Cuando las economías tienen una alta calidad institucional, se revierte el efecto positivo de la concentración del mercado y la diversificación de ingresos. El fortalecimiento de la calidad institucional de los países permite combinar la competencia entre bancos y la especialización en actividades tradicionales con mayor desempeño. Estos resultados son relevantes para la estabilidad bancaria y para el diseño de políticas financieras, dado que el marco institucional incluye canales directos e indirectos que afectan el comportamiento general y las estrategias de los bancos en la industria.